Treinamento físico resistido previne hipertensão arterial e melhora modulação autonômica cardíaca em ratos diabéticos induzidos pela aloxana - Barreto, André Sales (2010)
The aim of this study was to evaluate the effects of resistance training on blood pressure, ventricular repolarization, baroreflex sensitivity and cardiac autonomic balance in diabetic rats. Cardiovascular evaluation was performed in conscious trained and sedentary animals, 8 weeks after the onset of diabetes with alloxan or control animals. The resistance training consisted of 3 sets of 10 repetitions performed at 40% of one repetition maximum test, 3 days/wk over 8 wks in squattraining apparatus. Blood pressure was monitored for 30 min 48 h after the last training session or time control. Baroreflex sensitivity was analyzed by sequence method and cardiac autonomic balance was assessed by heart rate variability in the frequency domain. After 8 wks, the diabetes significantly increased glycemia (from 83 ± 8 to 381 ± 41 mg/dl, p<0.05), mean blood pressure (from 104.7 ± 5.4 to 125.1 ± 5.4 mmHg, p<0.05), QTc interval (from 4.4 ± 0.1 to 5.1 ± 0.1 ms, p<0.05), reduced baroreflex sensitivity (from 2.01 ± 0.3 to 0.38 ± 0.1 ms/mmHg, p<0.05) and impaired the cardiac autonomic balance. Resistance training was able to produce significant reduction on the glycemia (270 ± 17 mg/dl, p<0.05), prevented the increase of mean blood pressure (108 ± 3 mmHg, p<0.001) and QTc interval (4.6 ± 0.1 ms, p<0.01), the reduction of baroreflex sensitivity (2.63 ± 0.5 ms/mmHg, p<0.01) and disturbance on the cardiac autonomic balance. These results suggest that resistance training promotes a better glycemic control, prevents hypertension and improves baroreflex sensitivity and cardiac autonomic balance in alloxan diabetic rats.